Have We Passed Peak Capitalism? - Blair Fix (Economics from the Top Down, 2022)
Among leftists, predicting the end of capitalism is a favorite parlor game. For example, as a graduate student in the 2010s, I remember discovering the 1976 edition of Marx's Capital and being struck by the introduction. Written by the Belgian Marxist Ernest Mandel, the foreword concluded that it was `most unlikely' that capitalism would survive another half-century. This prediction (and many like it) did not age well. What capitalism's critics often misunderstand is that social orders rarely `die'. More often, they fade into irrelevance. Just as no one can point to the end-date of feudalism, it seems unlikely that capitalism will have a decisive `finish'. But what it may have is a peak. The goal of this post is to chart the rise (and potential peak) of `capitalism' … as I understand it. This caveat is key. To study a social system, we must first define it. To many people, capitalism is a `mode of production' (a definition inherited from Marx). The view that I take here, however, is that capitalism is primarily an ideology — or what Jonathan Nitzan and Shimshon Bichler call a `mode of power'. Capitalism is a set of ideas that justify the modern social order. Although there are many ways to chart the rise of capitalism, what interests me here is that it was the first major ideology to have spread during the era of mass publication. That means capitalism's rise (and potential peak) should be visible in the word frequency of written language. For example, as capitalism spread, we'd expect that capitalist jargon — words like `market' and `price' — should become more common. And feudal jargon — words like `fief' and `vassal' — should become less common. Now, I've chosen these specific words as an illustration. But for my actual analysis, I do not `choose' the jargon words. Instead, I choose a corpus of text that I believe encapsulates the ideology in question (capitalism or feudalism). And from there, I let the jargon of the text speak for itself. The basic idea is that jargon words are those that are both frequently used in a text corpus and overused relative to mainstream English. The first step of the analysis, then, is to select a corpus of ideological texts. To capture feudal ideology, I use a sample of 22 modern English bibles. I use modern translations because I don't want text that contains archaic words (like `thou'). And I use the Bible because christian theology formed the backbone of European feudalism.1 To capture capitalist ideology, I use a sample of 43 introductory economics textbooks. My claim is that these textbooks deal mostly in capitalist metaphysics; they describe a fantasy world of self-equilibrating markets in which each person earns what they produce.2 With my sample of biblical and economics text, I first isolate the jargon words of each corpus. Then I use the Google English corpus to measure how the frequency of this jargon has changed over time. (As a consistency check, I also analyze the text in paper titles on the Sci-Hub database and book titles in Library Genesis.) I find that over the last several centuries, biblical jargon became less popular and was slowly replaced by economics jargon. I also find evidence that the popularity of economics language peaked during the 1980s, and has since declined. Ominously, this peak coincides with an uptick in the popularity of biblical language. In simple terms, it seems that we (anglophones) are in the midst of an ideological transition.
Keywords: Z12; P16; Z13; Z1; A; 330; capitalism; economics; idelology; language; religion